CRIMINAL ACCOUNTABILITY FOR CIVIL SERVANT (CPNS) ADMISSION FRAUD - Abdillah, Akhmad Rezaldi Fahd; Astutik, Sri (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Several instances of misconduct have occurred, wherein certain individuals have taken advantage of public interest surrounding the CPNS registration process. In 2018, Defendants AD and SH profited IDR 200 million. In 2019, Defendant HB gained a profit of up to 5.7 billion Rupiah through the CPNS Recruitment mode, and in 2021, (ON) amassed a profit of 9.7 billion Rupiah. This research aims to analyze the application of the law to cases of fraud perpetrated against Candidates for Civil Servants (CPNS), and propose preventive measures to curb instances of fraud under the guise of a special pathway. The study is conducted through both normative and sociological legal research, utilizing a sociological interpretive approach. The Statute Approach and Case Approach are employed in this study. Legal material is gathered using library techniques, and the analysis of legal materials is performed using qualitative methods. The study's findings reveal that: (1) CPNS registration is strictly free of charge, and any claims suggesting the availability of internal routes for assistance are baseless. Perpetrators of such acts are subject to charges under Article 378 of the Criminal Code, which involves deceiving and causing harm to others. (2) Candidates applying for CPNS positions need not seek any special means to pass the selection process, as the principle of Bureaucratic Reform within the state civil apparatus prohibits any form of illicit practice.